Fertilization and male fertility in the rotifer Brachionus calyciflorus in the presence of three environmental endocrines. (April 2019) - Jin, Sichen; Shao, Li; Song, Xiaoping; Xiao, Jiahua; Ouyang, Kai; Zhang, Kailei; Yang, Jiaxin
Abstract: Many studies investigated the effects of environmental endocrine disruptors with the rotifer Brachionus calyciflorus . However, they focused on the reproductive behavior of rotifers, especially male–female fertilization, as a parameter in ecotoxicological and endocrine studies. In the present study, we used two environmental hormones (progesterone and testosterone) and one nonsteroidal antiandrogen (flutamide) at five different concentrations (0.5, 1, 2, 4, and 6 mg/L) to study the reproductive behavioral parameters of male rotifers. The average swimming speed of male rotifers in the blank group was 1.14 ± 0.43 mm/s. After exposure for 1 h, testosterone improved the swimming speed of males, with the greatest effect at a concentration of 2–4 mg/L, whereas flutamide and progesterone inhibited the swimming speed. Copulatory behavior experiments showed that, compared with the control group, the recognition ability of males was improved by testosterone at 1, 2, and 3 h ( P  < 0.05). After 4, 5, and 6 h, progesterone substantially suppressed the mating recognition ability of males, where the density of each group was extremely low at 6 h. Flutamide had a similar effect on the mating recognition ability of male rotifers as that of progesterone. The male fertilization rate in B. calyciflorus increased significantly under testosterone exposure at different concentrations ( P  < 0.05), with the highest level at 2 mg/L (male fertility rate = 48.61 ± 3.18%). The fertilization rate of male rotifers was suppressed by both progesterone and flutamide ( P  < 0.05), and higher drug concentrations had stronger suppressive effects. Highlights: This study supports relationships between endocrine disruptors and reproductive ability and provides a evaluation method in reproductive toxicology in rotifer. We used three environmental hormones to study the reproductive behavioral parameters of rotifers. We hope this research can provide a reference for the assessment of male rotifers in reproductive toxicology.